Hans Christoffel: “Kapten Kecil Penakluk Rimba” dalam Historiografi Kolonial Hindia Belanda - Durinx, Willy; Kozok, Uli (Department of History, Faculty of Humanities, Diponegoro University, 2025)
Hans Christoffel, a Swiss-born officer in the Royal Netherlands East Indies Army (KNIL), served from 1886 to 1910 and left a deeply ambivalent legacy shaped by both acclaim and notoriety. Nicknamed the “Acehnese Tiger” for his severe methods during the Aceh War, Christoffel rose rapidly through the ranks, becoming a highly decorated commander in the elite Korps Marechaussee te Voet, a unit established to suppress guerrilla resistance in the Dutch East Indies. Renowned for his innovative counter-guerrilla strategies as well as his ruthless tactics, including hostage-taking and violent pacification campaigns, he acquired a formidable reputation among both colonial authorities and Acehnese opponents. This article traces Christoffel’s transformation from a feared agent of colonial violence into a later-life spiritualist who publicly renounced his militarized past. Situating his career within the broader framework of Dutch Ethical Policy and the contested implementation of Pax Neerlandica, the study draws on colonial reports, newspaper accounts, and ethnographic museum collections to critically examine the entanglements of violence, colonial governance, and personal moral reorientation in the life of a figure once known as the “Flying Swiss.”